2022
DOI: 10.3390/metabo12010065
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between the Gut Microbiome and Bile Acids in Cardiometabolic Diseases

Abstract: Cardio-metabolic diseases (CMD) are a spectrum of diseases (e.g., type 2 diabetes, atherosclerosis, non-alcohol fatty liver disease (NAFLD), and metabolic syndrome) that are among the leading causes of morbidity and mortality worldwide. It has long been known that bile acids (BA), which are endogenously produced signalling molecules from cholesterol, can affect CMD risk and progression and directly affect the gut microbiome (GM). Moreover, studies focusing on the GM and CMD risk have dramatically increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 108 publications
(125 reference statements)
0
16
0
Order By: Relevance
“…There is a strong biochemical relationship between BAs and gut microbiota. Some gut microbiota in healthy people can convert conjugated BAs into free BAs, and can transform BAs into secondary BAs with the help of bile salt hydrolase (BSH) and cholesterol 7-alpha hydroxy-lase (CYP7A1) [ 147 ], so as to reduce blood cholesterol by affecting the enterohepatic circulation of BAs [ 148 , 149 ]. Besides, the gut microbiota affects the metabolism of BAs by regulating the activity of BSH to reduce LDL cholesterol levels [ 150 ].…”
Section: The Role Of the Gut Microbiota In Health And Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong biochemical relationship between BAs and gut microbiota. Some gut microbiota in healthy people can convert conjugated BAs into free BAs, and can transform BAs into secondary BAs with the help of bile salt hydrolase (BSH) and cholesterol 7-alpha hydroxy-lase (CYP7A1) [ 147 ], so as to reduce blood cholesterol by affecting the enterohepatic circulation of BAs [ 148 , 149 ]. Besides, the gut microbiota affects the metabolism of BAs by regulating the activity of BSH to reduce LDL cholesterol levels [ 150 ].…”
Section: The Role Of the Gut Microbiota In Health And Diseasesmentioning
confidence: 99%
“…It remains unclear how the gut microbiota and BAs profiles interact with each other and whether the interaction is associated with obesity [ 147 ]. Mice fed BAs exhibited obesity and a composition change in the obesity-associated gut microbiota, which is similar to high-fat diet-fed mice [ 216 , 217 ].…”
Section: The Gut Microbiota and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…The GM is a potential controller of wellness and disease. As demonstrated by experimental, clinical, and epidemiological evidence, a dysbiotic microbiota (i.e., a microbiota that deviates from the “eubiotic” status in terms of diversity and functionality [ 11 ]) is implicated in a range of diseases in adults, including inflammatory bowel disease [ 12 , 13 ], arthritis [ 14 ], cancer [ 15 ], neurological and neuropsychiatric disorders [ 16 ], cardiometabolic [ 17 ] and cardiovascular [ 18 ] disease, obesity [ 19 ], type 2 diabetes [ 20 , 21 , 22 ], and, as detailed below, infertility.…”
Section: Gut Microbiota: a New Player In Townmentioning
confidence: 99%
“…An increasing number of clinical studies have suggested that the gut microbiota and microbial metabolites are significantly different between patients with CMD and normal subjects. 25 , 26 , 27 , 28 A recent study revealed microbiome and metabolome features of the CMD spectrum. Patients with CMD already exhibit microbiota changes such as reduced bacterial cell counts and loss of microbial function in the early stages of their metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%